ASPEK-ASPEK SOSIOLOGIK SISTEM HUKUM NASIONAL (Tinjauan Kritis Terhadap Kasus Bank Century) - Noor Aziz Said (Faculty of Law, Universitas Jenderal Soedirman, 2010)
National law system professes the modern precept. The existence of modern law was integrally with the modern concept, which was the analytical legal positivism or the rechtdogmatiek and the political atmosphere which hegemony the XIX century, which is: “Liberalism”. Liberalism as a fundament of modern law focused in individual freedom and managing lives by preserving freedom and the sustainably. Liberal values and individual freedom have become paradigm inside the modern law system. And sociologic perspective, modern law existance with liberalism is a reflection of political interaction pattern, economic, social, and culture and preserving the interaction, it clearly that law contain with class characteristic. Law system was not integration media but creating and strenght the undistributed and social jealousy, and instituted privilege. The impact is law interaction no longer reflecting the equal relation but oriented to repressive based on power or asymmetry and negative sanction.Keyword: liberalism, class freedom, repressive, right